Quality Changes in Gamma Irradiated Marinades of Anchovy (Engraulis anchoita) during Refrigerated Storage - Tomac, Alejandra (2015)
The effect of gamma irradiation (0, 1.8, and 3.3 kGy) on the microbiological, chemical, and color characteristics of marinated (7% acetic acid and 10% NaCl) and vacuum-packed anchovy fillets was analyzed during 20 months of refrigerated storage (4 Â± 1Â°C). Acidity, pH, water activity (aw), total volatile basic nitrogen (TVBN), lipid oxidation, and color parameters were determined. Mesophilic and psychrotrophic bacteria, sulphite-reducing clostridia, total and fecal coliforms, Staphylococcus spp., yeasts, and molds were investigated. Gamma irradiation reduced the initial mesophilic bacterial counts and inhibited mesophils growth during 20 months. As a result, the production of TVBN during storage was lower in irradiated samples than in control. Also, lipid oxidation was lower in irradiated samples than in nonirradiated. The color of anchovy fillets was not affected by the irradiation treatment. Even if nonirradiated anchovy fillets presented a high stability in comparison with the traditional product (in flasks with vegetable oil and spices), gamma irradiation improved the microbiological and chemical quality of anchovy fillet marinades without inducing changes on its characteristic color for 20 months.